La formación continua de los docentes para la inclusión de los estudiantes con necesidades educativas especiales del bachillerato técnico en informática de la unidad educativa nueve de octubre de Guayaquil - Bedor Espinoza, Laura Patricia (2018)
Education in all levels is an important element of social integration and therefor a universally known component of the State that shows clear ideological attributes. The educational practice must account for all those aspects highlighting the complexity of any attempt of realization. This investigation covers the special educational needs for the technical high school of informatics, “Nueve de Octubre”, in Guayaquil……….